Advanced manufacturing an ICT and systems perspective /ceditors, Marco Taisch, Klaus-Dieter Thoben, Marco Montorio - Taisch, Marco; Thoben, K.-D; Montorio, Marco (Balkema-proceedings and monographs in engineering, water, and earth sciences., 2007)
Manufacturing plays a vital role in European economy and society, and is expected to continue as a major generator of wealth in the foreseeable future. A competitive manufacturing industry is essential for the prosperity of Europe, especially in the face of accelerating deindustrialisation. This book provides a broad vision of the future of manufacturing, analysed from a system-management viewpoint and with a special focus on ICT-related matters. Each contribution presents a complex and multidisciplinary research domain from a specific perspective.